2013
DOI: 10.3109/2000656x.2013.848809
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular reconstruction using custom-made titanium mesh tray and particulate cancellous bone and marrow harvested from bilateral posterior ilia

Abstract: The objective of this study is to evaluate usefulness of mandibular reconstructions using a custom-made titanium mesh (Ti-mesh) tray and particulate cancellous bone and marrow (PCBM). A consecutive nine patients who underwent mandibular reconstruction were enrolled in this study. They were five men and four women (mean age: 53.9 years). Virtual reality simulation was performed using computer software based on the pre-operative computed tomography data. A 3-dimensional (3-D) skull model was constructed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…CAD/CAM techniques and virtual planning methods provided the surgeons with a virtual environment for preoperative planning, reduced the surgical procedure time and related costs and yielded enhanced precision in restoring facial symmetry . Several complications were reported using pre‐adapted titanium meshes on a skull model, including a difficult and time‐consuming bending technique and fracture of the titanium mesh due to decreased strength and increased flexibility with insufficient bone formation as a result of mobilization of the bone graft . The EBM patient‐specific titanium tray showed satisfactory results in providing a symmetrical facial appearance and contours postoperatively, decreased intra‐operative time, ease in fixation, excellent adaptation on the remaining bony segments with the aid of the mandibular resection template, maintenance of proper condylar positioning and occlusion, and finally a cost comparable to that of the conventional reconstruction plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAD/CAM techniques and virtual planning methods provided the surgeons with a virtual environment for preoperative planning, reduced the surgical procedure time and related costs and yielded enhanced precision in restoring facial symmetry . Several complications were reported using pre‐adapted titanium meshes on a skull model, including a difficult and time‐consuming bending technique and fracture of the titanium mesh due to decreased strength and increased flexibility with insufficient bone formation as a result of mobilization of the bone graft . The EBM patient‐specific titanium tray showed satisfactory results in providing a symmetrical facial appearance and contours postoperatively, decreased intra‐operative time, ease in fixation, excellent adaptation on the remaining bony segments with the aid of the mandibular resection template, maintenance of proper condylar positioning and occlusion, and finally a cost comparable to that of the conventional reconstruction plate.…”
Section: Discussionmentioning
confidence: 99%
“…A titanium mesh tray and the Dacron urethane tray are the most frequently used . However, their strength is not suitable for reconstruction of the mandibular discontinuity; thus, long‐term maxillo‐mandibular fixation or reinforcement with a reconstruction plate is needed to prevent fracture of the mesh/tray, especially in long span defects including the chin area …”
Section: Introductionmentioning
confidence: 99%
“…This method has major advantages over the conventional bending technique with respect to the mechanical strength of the titanium mesh tray, thus preventing titanium mesh fracture. To avoid this serious complication, Yamada et al [11] reported that combination repair with a titanium reconstruction plate or fabrication of a reinforced titanium mesh tray (e.g. double layered titanium mesh) was necessary for the cases of long-span defect of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Defects of the mandible caused by tumor, osteomyelitis, or severe trauma affect patients' quality of life both physiologically and psychologically. Various approaches for mandibular reconstruction, including reconstructive titanium plates, nonvascularized or vascularized bone grafts, and autogenous iliac bone grafts in combination with a ready-made titanium mesh trays, have been tried [10] [11]. The most common approach for mandibular reconstruction today is a vascularized-bone graft from the fibula and iliac crest [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…Applying these concepts, the medical industry has been mentioned in papers such as (Otawa et al 2015;Sutradhar et al 2014;Yamada et al 2014) however the collaborative design is something that hasn't been taken into the mass customization conceptual space mainly the speed of converting medical imaging data to usable CAD file for use in additive manufacturing. With the use of 3D scanning and increased software and 3D printing capabilities, these concepts can be applied.…”
Section: Introductionmentioning
confidence: 99%